Labor income risk and the reluctance of fouseholds to invest in risky financial assets: A panel data analysis - Gideon Becker; Thomas Dimpfl (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We investigate the determinants of a household's decision on whether to invest in risky financial assets. Financial theory suggests that with increasing labor income risk, the reluctance of households to hold stocks increases. We propose to measure income risk as the observed variation of household income over a five year period. We find that indeed higher income risk reduces the propensity to invest in stocks. However, when controlling for household heterogeneity as well as subjective measures of a household's financial situation (income satisfaction, worries about financial situation), the impact of observed labor income variation vanishes.
urn:nbn:de:bsz:21-dspace-527718
Keywords: D14; D81; G11; 330; household finance; risky asset market participation; labor income risk; behavioral finance; unobserved heterogeneity